Prefeasibility study for mesino lemon (Citrus aurantifolia) production in Acosta, and its marketing in CENADA, Costa Rica. - Briceño Quintana, Lucía (2018)
The objective of the present research was to determine the feasibility of producing Mesino lemon (Citrus aurantifolia) in the Acosta zone, and its commercialization in the National Center for Food Supply and Distribution (CENADA) located in Barreal de Heredia. In this regard, a study to determine the commercial, technical, environmental, legal and financial viability of the crop was conducted between March and June 2013, taking a 3 hectares plantation as the stage of production. Through market research it was determined that the product has a potential marketing, essentially in CENADA; also thanks to the technical study, it was concluded that the location of the project area (Acosta) is suitable for the activity because the growing conditions are compatible with the cultivation; the environmental study reflected the importance of applying good agricultural practices through all stages of production, so that a minimal negative impact on the environment is achieved, as well as maximizing the potential ecological benefits; finally through the financial analysis it was determined that the project is feasible, introducing an IRR of 24,26% and an NPV of ₡142.852.045.